New route discovery design for routing misbehaviour prevention in multi-hop wireless sensor networks. (1st January 2014) - Ammayappan, Kavitha; Negi, Atul; Sastry, V.N.
This paper proposes a new secure route discovery protocol design for multi-hop wireless sensor networks (WSNs). It mainly prevents hidden channel and worm hole attacks. These two attacks are the main causes for non-plausible route setups. So far, no one has attempted to address the hidden channel attack in WSNs. Here, we use authentic neighbourhood and common authentic neighbours to prevent hidden channel and worm hole attacks. The requirement for the use of bandwidth is optimised through limited broadcasting design of the route discovery process. The correctness of the proposed protocol has been tested by AVISPA model checker. Simulation results of the proposed routing design ensures the effectiveness of the approach.